Textos integrados y narratologías míticas y posmodernas: algunos paralelismos - Martos Núñez, Eloy; Martos García, Alberto E. (Revista Chilena de Literatura, 2014)
This article deals with the integrated texts of cyclic tales and also the instruments and tools to catalog the components of fiction in a broad sense, the way to define the units of analysis (narratologies) and the poetics of each period, with the emphasis on readers’ responses to determine the modes of narrative texts. Narratological models of the folktale and its descriptive apparatus have been reviewed, along with other major narrative universes, such as serial narratives underlying sagas and television series. Other current factors, such as the practice of new readers and the entertainment industry, reveal the success of a postmodern discourse which is no longer focused on elucidating the elements of fiction of its own time, but interested in “collecting” them to cause the convergence of various expressive means. This porosity of categories and grouping criteria serves as a link between texts from different literary cultures –from orality to postmodern literary reinterpretation of ancient mythographies–, and allows us to draw parallels between mythic narratives and the narratives of postmodernism.